2021
DOI: 10.1109/access.2021.3098688
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Machine Learning Framework for Effective Prediction of Cardiovascular Diseases

Abstract: Cardiovascular diseases are considered as the most life-threatening syndromes with the highest mortality rate globally. Over a period of time, they have become very common and are now overstretching the healthcare systems of countries. The major factors of cardiovascular diseases are high blood pressure, family history, stress, age, gender, cholesterol, Body Mass Index (BMI), and unhealthy lifestyle. Based on these factors, researchers have proposed various approaches for early diagnosis. However, the accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The test results showed that MLDS has proven to be able to efficiently predict the risk of cardiovascular disease compared to five other different models. In the same context, Rahim et al [11] suggested a Machine Learning-based Cardiovascular Disease Diagnosis framework (MaLCaDD) to improve the prediction accuracy of cardiovascular diseases. Rahim et al stated that increasing the accuracy of the prediction using various feature selection and classification methods has taken the most attention of the researchers.…”
Section: Related Workmentioning
confidence: 99%
“…The test results showed that MLDS has proven to be able to efficiently predict the risk of cardiovascular disease compared to five other different models. In the same context, Rahim et al [11] suggested a Machine Learning-based Cardiovascular Disease Diagnosis framework (MaLCaDD) to improve the prediction accuracy of cardiovascular diseases. Rahim et al stated that increasing the accuracy of the prediction using various feature selection and classification methods has taken the most attention of the researchers.…”
Section: Related Workmentioning
confidence: 99%
“…It serves as a mean to reduce the variance of a single KNN estimator by introducing randomization into its construction procedure [31] and then makes an ensemble out of it. The mechanism of KNN algorithm itself is to find the k nn samples closest to the query sample to be predicted based on a distance metric [32]. Then it performs the prediction based on averaging the information of these k nn nearest neighbors.…”
Section: Model Selectionmentioning
confidence: 99%
“…It is necessary to evaluate the path loss value in a very short time, so that the spatial distribution of electromagnetic fields can be quickly updated in response to the propagation environment changes. The complexity associated with the ML-based algorithms is tabulated in Table 4 as presented in [32]. The ensemble methods generally multiply the complexity of the original model by the number of ensembles within the model and replace the training size by the size of each ensemble.…”
Section: Computational Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of k-nearest neighbor (KNN) and logistic regression is used for the ensemble learning framework that predict cardiovascular diseases. Data imbalance is managed via synthetic minority over-sampling technique (SMOTE) method [23]. Independent component analysis (ICA) is used for the dimensionality reduction to implement the lung cancer detection algorithm using the AdaBoost based ensemble learning method [24].…”
Section: Introductionmentioning
confidence: 99%